Human rights and migration in Peru: a constitutional analysis on equality and the challenges of integration - Vásquez Pérez, Albert (2025)
This research analyzes the relationship between human dignity, the principle of equality, and fundamental rights in the context of migration. Its main objective is to examine how the legal recognition of equality impacts access to fundamental rights by the migrant population, identifying normative and structural barriers that limit their exercise. A basic qualitative approach was used, with a non-experimental design based on observation and critical analysis of specialized sources. The study population included relevant doctrine, jurisprudence of the Constitutional Court and the Inter-American Court of Human Rights, as well as national and international regulations on equality and migration. The main findings show that, although international law establishes equality between nationals and foreigners, in practice restrictions persist that affect migrants' access to certain rights. The research concludes that the implementation of migration policies must balance state sovereignty with the protection of human dignity, avoiding discriminatory regulations that perpetuate exclusion.